Diverse Functions of IAA-Leucine Resistant PpILR1 Provide a Genic Basis for Auxin-Ethylene Crosstalk During Peach Fruit Ripening - Wang, Xiaobei; Meng, Junren; Deng, Li; Wang, Yan; Liu, Hui; Yao, Jia-Long; Nieuwenhuizen, Nicolaas Jacobus; Wang, Zhiqiang; Zeng, Wenfang (Frontiers in Plant Science, 2021)
Auxin and ethylene play critical roles in the ripening of peach (Prunus persica) fruit; however, the interaction between these two phytohormones is complex and not fully understood. Here, we isolated a peach ILR gene, PpILR1, which encodes an indole-3-acetic acid (IAA)-amino hydrolase. Functional analyses revealed that PpILR1 acts as a transcriptional activator of 1-amino cyclopropane-1-carboxylic acid synthase (PpACS1), and hydrolyzes auxin substrates to release free auxin. When Cys137 was changed to Ser137, PpILR1 failed to show hydrolase activity but continued to function as a transcriptional activator of PpACS1 in tobacco and peach transient expression assays. Furthermore, transgenic tomato plants overexpressing PpILR1 exhibited ethylene- and strigolactone-related phenotypes, including premature pedicel abscission, leaf and petiole epinasty, and advanced fruit ripening, which are consistent with increased expression of genes involved in ethylene biosynthesis and fruit ripening, as well as suppression of branching and growth of internodes (related to strigolactone biosynthesis). Collectively, these results provide novel insights into the role of IAA-amino acid hydrolases in plants, and position the PpILR1 protein at the junction of auxin and ethylene pathways during peach fruit ripening. These results could have substantial implications on peach fruit cultivation and storage in the future.